Study of Microstructure and rheological properties of gels sabalo protein concentrate (prochilodus platensis) relative to the washing step and NaHCO3 solutions H3PO4 - Reinheimer, María Agustina; Medina, José R.; Beresvil, Luciana; Pérez, Gustavo A. (Nexo Revista Científica, 2013)
The fish protein concentrate (FPC), is minced fish muscle and free of bones, skin, bones and dark meat, which is washed several times with water and drained to the original water ratio. The paper studies the effect on the physical and chemical composition, the microstructure and functional properties of gels FPC using different wash water solutions in obtaining tarpon FPC (Prochilodus platensis). Were evaluated protein extractions during washing, and analysis of the functional properties of the gels obtained. FPC gels obtained by the method shad wash (0.05% H3PO4, 0.2% NaHCO3 and 0.2% NaCl) had an acceptable content of protein, lower fat content, and more acceptable texture, rheology and confirmed by microstructure, showing improvements over the gels obtained by the conventional method. DOI: http://dx.doi.org/10.5377/nexo.v26i1.1210